The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.4236/ojas.2015.54048
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oocyte Recovery Techniques on <i>in Vitro</i> Production of Swine Embryos

Abstract: In vitro production of swine embryos is a valuable tool to generate clones and genetically modified pigs during a short period of time. However, the efficiency of the existing methods is extremely low and the oocyte quality and quantity represent important obstacles on the success of in vitro production of embryos. Therefore, the aim of this study was to compare the in vitro maturation, fertilization and subsequent embryo development rates of oocytes recovered by ovary slicing or follicular aspiration. The ooc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…In our investigation of the recovery rates of oocytes, we found that A and B oocytes formed only a minority of the total yield (8.1% and 24.1% of A and B, respectively, Figure 5 ), which is in line with previous findings (Lin et al., 2016 ). Our comparisons of oocytes recovered using different aspiration pressures and needle gauges (Figure 5 , Table 1 ) indicate that both factors affect oocyte recovery; this supports previous work that identified a negative correlation between the size of the COCs retrieved and the aspiration pressure, with higher pressures increasing the incidence of denuded oocytes (Brüssow et al., 1997 ; Marques et al., 2015 ). Furthermore, these data suggest the existence of a compromise between recovery rates and oocyte quality, with quality maximised by lower pressures.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In our investigation of the recovery rates of oocytes, we found that A and B oocytes formed only a minority of the total yield (8.1% and 24.1% of A and B, respectively, Figure 5 ), which is in line with previous findings (Lin et al., 2016 ). Our comparisons of oocytes recovered using different aspiration pressures and needle gauges (Figure 5 , Table 1 ) indicate that both factors affect oocyte recovery; this supports previous work that identified a negative correlation between the size of the COCs retrieved and the aspiration pressure, with higher pressures increasing the incidence of denuded oocytes (Brüssow et al., 1997 ; Marques et al., 2015 ). Furthermore, these data suggest the existence of a compromise between recovery rates and oocyte quality, with quality maximised by lower pressures.…”
Section: Discussionsupporting
confidence: 87%
“…Aspiration methods can be either manual, using a syringe barrel and needle, or assisted, using a negative pressure aspiration pump and attached needle. Automated aspiration procedures generally allow for a more consistent collection environment when compared to manual aspiration, which is prone to inter‐operator variability (Marques et al., 2015 ). The oocytes retrieved for IVM are found in combination with cumulus cells (CCs), forming the cumulus oocyte complex (COC).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can then be deduced that the slicing method provides the highest amount of oocytes during collection when compared to aspiration. Marques et al (2015) found similar results, showing that the slicing method produced a higher amount of oocytes than the aspiration method.…”
Section: Resultsmentioning
confidence: 57%
“…These findings were not in accordance with Lekola (2015) who found no significant differences between the quality of bovine oocytes when using the aspiration or slicing method. Marques et al (2015) found that the aspiration method was the method of choice for later reproductive technologies (p = 0.0395). While they found the slicing method to produce a higher quantity of oocytes, their later study showed that there were no differences between oocyte recovery methods until day 7 post IVF.…”
Section: Resultsmentioning
confidence: 98%